a Diophantine Equation (Fermat)

Solve the following diophantine equation: y 2 + 2 = x 3 y^2 + 2 = x^3

  • Let A A be the set A = { ( x , y ) Z 2 / y 2 + 2 = x 3 } A = \{(x,y) \in \mathbb{Z}^2 \text{ / } y^2 + 2 = x^3\} which is a countable set.

  • Find all the elements of A A and enter ( x , y ) A ( x + y ) \displaystyle \sum_{(x,y) \in A} (x + y)


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Jun 4, 2017

The ring Z [ i 2 ] \mathbb{Z}[i \sqrt{2}] is a Euclidean domain, and we want to find x , y Z x,y \in \mathbb{Z} such that x 3 = ( y + i 2 ) ( y i 2 ) x^3 = (y + i\sqrt{2})(y - i\sqrt{2}) . The multiplicative norm function for Z [ i 2 ] \mathbb{Z}[i \sqrt{2}] is N ( a + i b 2 ) = a 2 + 2 b 2 N(a + ib\sqrt{2}) = a^2 + 2b^2 .

Suppose that z z is an element of Z [ i 2 ] \mathbb{Z}[i \sqrt{2}] which is a common factor of y + i 2 y + i\sqrt{2} and y i 2 y - i\sqrt{2} . Then z z must divide 2 i 2 2i\sqrt{2} , and so N ( z ) N(z) must divide 8 8 . If N ( z ) = 2 N(z) = 2 we must have z = ± i 2 z = \pm i\sqrt{2} . This would imply that y y was even, and hence that x 3 = y 2 + 2 2 ( m o d 4 ) x^3 = y^2 + 2 \equiv 2 \pmod{4} , which is impossible. If N ( z ) = 4 N(z) = 4 we must have z = ± 2 z = \pm2 , which is not possible. If N ( z ) = 8 N(z) = 8 we must have z = ± 2 i 2 z = \pm2i\sqrt{2} , which is not possible either. Thus N ( z ) = 1 N(z) = 1 , and so z z is a unit. Thus y + i 2 y+i\sqrt{2} and y i 2 y-i\sqrt{2} are coprime in Z [ i 2 ] \mathbb{Z}[i \sqrt{2}] . Since their product x 3 x^3 is a cube, it follows that each of y + i 2 y + i\sqrt{2} and y i 2 y - i\sqrt{2} is a cube in Z [ i 2 ] \mathbb{Z}[i \sqrt{2}] .

Thus we can find u , v Z u,v \in \mathbb{Z} such that y + i 2 = ( u + i v 2 ) 3 = u ( u 2 6 v 2 ) + v ( 3 u 2 2 v 2 ) i 2 y + i\sqrt{2} \; = \; (u + iv\sqrt{2})^3 \; = \; u(u^2 - 6v^2) + v(3u^2 - 2v^2)i\sqrt{2} so that y = u ( u 2 6 v 2 ) v ( 3 u 2 2 v 2 ) = 1 y \; = \; u(u^2 - 6v^2) \hspace{2cm} v(3u^2 - 2v^2) \; = \; 1 From the second equation we see that v = ± 1 v = \pm1 and that 3 u 2 2 v 2 = ± 1 3u^2 - 2v^2 = \pm1 , and so 3 u 2 = 2 ± 1 3u^2 = 2 \pm 1 . Thus it follows that v = 1 v=1 and u 2 = 1 u^2 = 1 , so that u = ± 1 u = \pm1 , and hence y = 5 y = \mp5 . For each of these values of y y , we have x = 3 x=3 .

Thus A = { ( 3 , 5 ) , ( 3 , 5 ) } A \,=\, \big\{(3,5),(3,-5)\big\} , and so the answer is 3 + 5 + 3 5 = 6 3+5 + 3 - 5 = \boxed{6} .

This is incredible... Your solution is essentially the same as mine.

Guillermo Templado - 4 years ago

Log in to reply

Well, this is a known problem (originally discussed by Fermat), and using Z [ i 2 ] \mathbb{Z}[i\sqrt{2}] is probably the standard modern solution technique.

Mark Hennings - 4 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...